KAJIAN TINDAKAN KONSERVASI LAHAN DAN PEMUPUKAN SERTA PENGARUHNYA TERHADAP PRODUKSI KOPI ROBUSTA (coffea canephora) DI KECAMATAN SILIMA PUNGGA-PUNGGA, KABUPATEN DAIRI, SUMATERA UTARA - Ardianta Ginting; Syafrinal Syafrinal; Al Ikhsan Amri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aims to study the effect of conservation technique and fertilised which was done by the farmer to coffee production. This research was conducted at Silima Pungga-pungga, Dairi, North Sumatera. This research was done In February-March 2017. This research was conducted with Survey Method by taking some farmers as research sample. Sample was taken by used Purposive Sampling Method on level 5%. Sample criteration is the farmer in slope farmland (0-8)%, (9-16)% and (17-25)% with total sample 90. This research also used primary and secondary data which are taken by interview technique with the questionnaire and observation technique were direct field. Based on the result of the research was conducted at Silima Pungga-pungga, the researcher can conclude that the conservation technique and fertilised which were done by farmer show the significant effect to the coffee production itself on farmland slope (0-8)% and (9-16)% farmland slope while on farmland slope (17-25)% conservation technique and fertilised didn’t show the significant effect to the coffee production itself. Based on regression analysis can be gotten regression similarityfor the farmland slope (0-8)% is Y=0,286+0,097X1+0,578X2, (9-16)% is Y=1,961+0,177X1+0,439X2, (17-25)% is Y=1,403+0,020X1+0,213X2, it means that conservation technique and fertilised have positif value in every farmland slope.Keywords: Robusta Coffee, Conservation technique, Fertilised.